THE EFFECT OF SOCIAL MEDIA FOR CUSTOMER RELATIONSHIP MANAGEMENT ON SME’S PERFORMANCE WITH SOCIAL COMPETENCE AND SALES INTENSITY AS MODERATING VARIABLES - Satyagraha, Bernardus Aldy; Soelaiman, Lydiawati (International Journal of Application on Economics and Business, 2023)
Advances in information technology help companies better understand their customers. Social media is one of many ways MSMEs improve their business performance by approaching consumers through Customer Relationship Management (CRM). Truly, an entrepreneur needs social competence to be able to interact well and possess sales intensity to increase the frequency of interaction. Based on this, this research aims to examine the impact of using social media for CRM on MSMEs’ performance with social competence and sales intensity as moderating variables. The sampling technique used for this research is non-probability sampling and the data were collected through questionnaire in the form of a google form distributed to 97 MSME in Jakarta. The results from structural equation modeling (SEM) method and processed using the SmartPLS version 3.3.3 application showed that social media for CRM, social competence and sales intensity positively influence MSMEs’ business performance in Jakarta. This research also showed that social competence doesn’t moderate the influence of using social media for CRM on MSMEs’ business performance in Jakarta, and the sales intensity weakens the effect of using social media for CRM on business performance of MSMEs in Jakarta.